Carotid Intraplaque Neovascularization and Future Vascular Events in Patients With Asymptomatic Carotid Stenosis - Cui, Liuping; Xing, Yingqi; Wang, Lijuan; Liu, Kangding; Chen, Hongxiu; Li, Cong; Chen, Ying (Frontiers in Pharmacology, 2022)
Objective: Intraplaque neovascularization is a marker of plaque vulnerability and is used to predict the risk of future vascular events in patients with symptomatic carotid stenosis; however, its association with asymptomatic carotid stenosis has not been prospectively evaluated. Therefore, this study aimed to explore the association between intraplaque neovascularization assessed using contrast-enhanced ultrasound and the occurrence of future ischemic events in asymptomatic patients diagnosed with carotid stenosis. Methods: We recruited patients with asymptomatic carotid stenosis from our center. Contrast-enhanced ultrasound was performed at baseline. The outcomes were ischemic stroke and cardiovascular events. We plotted Kaplan-Meier survival curves and performed a log-rank test to compare endpoint event probability in patients with and without grade 2 intraplaque neovascularization. Univariate and multivariate Cox proportional hazards models were used to assess predictors of future vascular events. Results: The data of 50 participants were included in the analysis (median follow-up, 43.7 months). Endpoint events occurred in 12 participants (24%). The Kaplan-Meier survival curves showed that patients with grade 2 intraplaque neovascularization had a higher probability of future vascular events than those with grades 0 and 1 (p < .05). Grade 2 intraplaque neovascularization (hazard ratio: 4.530, 95% confidence interval, 1.337–15.343, p < .05) was an independent predictor of future vascular events in patients with asymptomatic carotid stenosis. Conclusion: Grade 2 intraplaque neovascularization assessed using contrast-enhanced ultrasound independently predicted future ischemic events in patients with asymptomatic carotid stenosis, and contrast-enhanced ultrasound may be an effective screening method to identify high-risk subgroups of patients with asymptomatic carotid stenosis.